2019
DOI: 10.3389/fpsyg.2019.00537
|View full text |Cite
|
Sign up to set email alerts
|

Does Exposure to Foreign Culture Influence Creativity? Maybe It's Not Only Due to Concept Expansion

Abstract: Multicultural experience refers to those experiences gained through individuals' contact with other cultures. This study focused on exploring whether knowledge of different cultures can improve creative performance-and also how multicultural experiences influenced this performance through changes in individual's physiological mechanisms. Study 1 explored the influence of different cultural priming on creative story-writing tasks. Eighty-nine Chinese college students were randomly assigned to 4 conditions: sole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
3
0
2
Order By: Relevance
“…This exploration can also be expanded to identify how differing time lengths in various cultures can affect one's food perception, food consumption, or food choice habits. Tan et al [130] were able to show that small exposures of individuals from an analytic culture to a more holistic culture affected individuals' physiological states, neural patterns, and creativity. Thus, if these parameters were all influenced by multicultural experiences of less than an hour, it would be expected that food perception and behavior would also be impacted, especially given that most multicultural experiences are much longer than one hour.…”
Section: Future Directionsmentioning
confidence: 99%
“…This exploration can also be expanded to identify how differing time lengths in various cultures can affect one's food perception, food consumption, or food choice habits. Tan et al [130] were able to show that small exposures of individuals from an analytic culture to a more holistic culture affected individuals' physiological states, neural patterns, and creativity. Thus, if these parameters were all influenced by multicultural experiences of less than an hour, it would be expected that food perception and behavior would also be impacted, especially given that most multicultural experiences are much longer than one hour.…”
Section: Future Directionsmentioning
confidence: 99%
“…Based on fMRI investigations, creativity has been linked to the co-participation of cognitive and thinking processes, which is related to multiple areas of the brain (Fink et al, 2010 ; Boccia et al, 2015 ; Ye et al, 2021b ). Furthermore, evidence from high-resolution EEG studies has shown that the brains of high-level creatives exhibit more right-hemispheric alpha activities than low-level creatives (Arden et al, 2010 ; Tan et al, 2019 ). Several studies have proposed that alpha activities can both promote inspiration and accelerate information collection, activities that are widely considered to comprise the optimum neurologic state of learning and thinking (Fiore et al, 2000 ; Jawed et al, 2019 ; Harada et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…La exposición a una nueva cultura podría provocar diferentes respuestas psicológicas en las que la ansiedad, la confusión y el choque cultural afectan a la salud mental de los individuos [41]. Este complejo proceso requiere de apoyo y acompañamiento profesional para superarlo.…”
Section: Investigaciónunclassified